Screening for Chitinase-Producing Bacteria (Asia Pacific Journal of Social Innovation, 2024)
Six acces~ions of bac~eria, belonging to four genera from the MicrobialCulture Collection and Services Laboratory of the National Institute of Malecular Biology and Bidtechnology (BIOTECH), UP, at Los Baftos were selected as chitinase-producing based on thei~ ability to show moderate to heavy gruwth and form moderate to large zone of clearing around colonies in chitin agar. The chitinolytic bacteria selected were: Bacillus circulans BIOTECH 1037 (5Bo)1 Arthrobacter luteus BIOTECH 1077 (6A1), B. circu:lans BIOTECH 1045 (7Bc),Strep~omyces griseus BIOTECH 1562 (9Sg), and Serratia·marcescens LPC19 BIOTECH 1748 '(11Sm) and S. marcescens LPM42 BIOTECH 1749(14SSm).